Pendekatan Bimbingan dalam Menangani Anak Berperilaku Bermasalah di Sekolah - Tabita Plaikari; Umiyani Kona, Yegelode Lauta, Yessy Mata, Petrus Mau Tellu Dony, Nehemia Fanpada, Yermia Samuel Waba (CV. Adiba Aisha Amira, 2025)
Problematic behavior in children is a major challenge in education, especially at the elementary school level. Children who exhibit deviant behaviors such as disturbing peers, disobeying rules, or displaying emotional instability can disrupt the teaching and learning process and create an unconducive classroom atmosphere. This study aims to identify effective guidance approaches in addressing students' behavioral issues at school, focusing on the role of teachers, collaboration with parents, and challenges encountered in the field. The research employed a qualitative descriptive method using interviews with a single respondent, a classroom teacher. The findings indicate that personal approaches, open communication, and collaboration between schools and parents are key in managing students’ behavioral issues. Additionally, teachers play a role as mediators in uncovering students' potentials and directing them towards positive activities. However, limitations in school support and external environments remain significant challenges. Therefore, synergy among schools, families, and communities is essential in creating a learning environment that supports the holistic development of children.